1999
DOI: 10.1016/s0168-6496(98)00119-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen source on the solubilization of different inorganic phosphates by an isolate of Penicillium rugulosum and two UV-induced mutants

Abstract: The mechanisms of action of mineral phosphate solubilization (MPS) were studied in the wild-type Mps Penicillium rugulosum strain IR94-MF1 and in negative (Mps 3 ) and superpositive (Mps ) mutants derived from it. MPS activities were measured in liquid media using sucrose as C source, four N (arginine, nitrate, nitrate+ammonium and ammonium) and P sources (KH P PO R , hydroxyapatite, FePO R and AlPO R ). Ammonium significantly (P 6 0.01) decreased phosphate solubilization, and this activity was 1^66 times high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 23 publications
8
68
0
8
Order By: Relevance
“…On the other hand, Reyes et al, (1999) and Yadav and Tarafdar (2003) found a negative correlation between microbial dry mass and the concentration of soluble P obtained from the dissolution of RP. This coincides with the results obtained in the present study, since the RP with the greatest dissolution (Norte de Santander RP) generated a lower microbial dry mass than that found with the Boyaca RP.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…On the other hand, Reyes et al, (1999) and Yadav and Tarafdar (2003) found a negative correlation between microbial dry mass and the concentration of soluble P obtained from the dissolution of RP. This coincides with the results obtained in the present study, since the RP with the greatest dissolution (Norte de Santander RP) generated a lower microbial dry mass than that found with the Boyaca RP.…”
Section: Discussionmentioning
confidence: 93%
“…Evidence of these mechanisms in the present study is seen in the decrease in pH from an initial value of 5.09 to 3.58 with the use of A. niger. In regards to this fungus, there are authors who speak of the production of organic acids, particularly citric, oxalic and gluconic acids, as its dissolution mechanism (Sperber, 1958;Illmer and Schinner, 1995;Reyes et al, 1999;Seshadri et al, 2004). Narsian and Patel (2000), Reddy et al, (2002), Barroso and Nahas (2005) and Mittal et al, (2008) reported that relative efficiency in the dissolution of RP depends on the type of RP and the type of microorganism, as well as the quantity and quality of the acid secreted into the medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The commonly isolated phosphate solubilizing bacteria (PSB) generally belong to the genera Bacillus or Pseudomonas (Peix et al 2004;Chen et al 2006). In addition, a number of fungal species solubilize P; these species generally belong to the genera Aspergillus or Penicillium (Reyes et al 1999;Vazquez et al 2000). The significant positive correlation between utilization of RP by plants and the population density of PSB enhanced by compost amendments in Andosols was shown by Wickramatilake et al (2010).…”
Section: Introductionmentioning
confidence: 99%
“…Whitelaw et al (1999) verificaram que Penicillium radicum solubilizou Ca 3 (PO 4 ) 2 , CaHPO 4 , FePO 4 .4H 2 O e AlPO 4 em meio líquido. Reyes et al (1999) encontraram correlação positiva entre a solubilização de fosfatos por Penicillium rugulosum e a produção de ácido glucônico ou cítrico.…”
unclassified